Gyroscope ASIC - Kong, Xiaolu (2015)
Micro-electromechanical gyroscope becomes one of the most valuable segments of the micro sensor market. The drive loop circuit is designed to support MEMS gyroscope to start self-oscillation with certain constant frequency and amplitude. In this final year project, the analog drive loop circuit of the electrical MEMS gyroscope supporting system is designed and simulated. An analog phase locked loop (PLL) is introduced into this drive loop for oscillation activation and maintenance. PLL is designed based on the negative feedback loop containing components including: phase detector (PD), low-pass filter (LPF) and analog voltage control oscillator (VCO). In addition, to get a signal with 90 degree phase shift for sense modular, a phase shifter is designed. These components are constructed at the transistors level and simulated in Cadence. At last a digital drive loop circuit is soldered on printed circuit board (PCB) using commercial electrical instruments and tested with MEMS gyroscope.